1997
DOI: 10.1021/bi970825u
|View full text |Cite
|
Sign up to set email alerts
|

Tight Binding of Folate Substrates and Inhibitors to Recombinant Mouse Glycinamide Ribonucleotide Formyltransferase

Abstract: The binding of the prototypical folate inhibitor of de novo purine synthesis, 5,10-dideazatetrahydrofolate (DDATHF), and its hexaglutamate to recombinant trifunctional mouse glycinamide ribonucleotide formyltransferase (rmGARFT) was studied by equilibrium dialysis and by steady-state kinetics using sensitive assays that allowed initial rate calculations. rmGARFT was expressed in insect cells infected with a recombinant baculovirus and purified by a two-step procedure that allowed production of about 25 mg of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
(56 reference statements)
2
28
0
Order By: Relevance
“…The more marked resistance of ZD1694 in these cell lines likely reflects the fact that the polyglutamates of ZD1694 bind to thymidylate synthase about 100 times tighter than the ZD1694 monoglutamate. On the other hand, DDATHF and LY309887 are tight binding inhibitors of GART prior to metabolism (31), and become better enzyme inhibitors with polyglutamation (31), but to a lesser degree than does ZD1694 (28).…”
Section: Discussionmentioning
confidence: 99%
“…The more marked resistance of ZD1694 in these cell lines likely reflects the fact that the polyglutamates of ZD1694 bind to thymidylate synthase about 100 times tighter than the ZD1694 monoglutamate. On the other hand, DDATHF and LY309887 are tight binding inhibitors of GART prior to metabolism (31), and become better enzyme inhibitors with polyglutamation (31), but to a lesser degree than does ZD1694 (28).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of lometrexol had been suggested by G. Peter Beardsley to his former mentor Ted Taylor as a potential antifolate, initially thought to be a likely inhibitor of thymidylate synthase; to their surprise, it was not, but it was a potent inhibitor of tumor cell growth (28). Cell culture experiments (28,29), then direct enzymology on isolated (29,30) and recombinant (31) proteins in the laboratory of one of the authors, showed that lometrexol was the first potent antifolate inhibitory to purine synthesis due to its direct suppression of glycinamide ribonucleotide transferase (GARFT) activity. Because this was not a nucleotide analogue, it was considered not to pose a mutagenic nor carcinogenic threat.…”
Section: Origins Of Pemetrexedmentioning
confidence: 99%
“…The content of H 4 PteGlu n and 5,10-CH 2 -H 4 PteGlu n was determined by this method, then the cellular levels of 10-CHO-H 4 PteGlu n were determined indirectly by quantitating the additional H 4 PteGlu n formed in the presence of excess GARFT and glycinamide ribonucleotide. Briefly, cell pellets containing 4 ϫ 10 6 cells were resuspended in 200 l of boiling 10 mM sodium phosphate buffer, pH 7.5, containing 0.1% Triton X-100, 1% 2-ME, and 1% freshly prepared sodium ascorbate.…”
Section: Synthesis Of 3 H-labeled (6r)-ddathf-mentioning
confidence: 99%
“…Kinetic analysis of GART inhibition was performed on GART purified by affinity chromatography from both cell lines. K i values were obtained from Dixon plots using K m values of 75 nM (4). Values are expressed as mean Ϯ S.D.…”
Section: Table II Activity and Kinetics Of Gart And Fpgs In L1210mentioning
confidence: 99%
See 1 more Smart Citation